2021
DOI: 10.3389/fneur.2021.692840
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Screening for Children With Suspected Auditory Processing Disorder: A Systematic Review

Abstract: Objective: This research aimed to provide evidence for the early identification and intervention of children at risk for auditory processing disorder (APD). Electrophysiological studies on children with suspected APDs were systematically reviewed to understand the different electrophysiological characteristics of children with suspected APDs.Methods: Computerized databases such as PubMed, Cochrane, MEDLINE, Web of Science, and EMBASE were searched for retrieval of articles since the establishment of the databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 122 publications
(169 reference statements)
0
6
0
1
Order By: Relevance
“…Electrophysiological assessment is a way of probing the central auditory nervous system and is a sensitive instrument to test the effectiveness of auditory training [ 10 , 24 ]. In this study, ABR click responses were used to ensure the integrity of the auditory pathway [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological assessment is a way of probing the central auditory nervous system and is a sensitive instrument to test the effectiveness of auditory training [ 10 , 24 ]. In this study, ABR click responses were used to ensure the integrity of the auditory pathway [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The click ABR can be a helpful electrophysiological tool in the detection of auditory nerve integrity; however, its use for the identification of children with auditory processing disorder has not yet been clearly demonstrated. Thus, it is important to conduct new studies using the ABR click to verify its effectiveness [ 10 ]. However, there are studies that highlight the possibility of evaluating auditory evoked potentials by investigating the binaural interaction component that might be able to determine the presence of auditory processing disorder earlier than behavioral analysis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al conducted a systematic review and found that there are seven testing modalities that rely on electrophysiology currently, including click-evoked auditory brainstem responses, frequency-following responses, the binaural interaction component of the auditory brainstem responses, middle-latency response, cortical auditory evoked potential, mismatch negativity, and P300 [ 58 ]. They found that all of these tests have the potential to be used for the diagnosis of APD, but more research is warranted to completely understand the results of the tests [ 58 ]. The development and implementation of standardized and objective electrophysiologic techniques for the diagnosis of APD is crucial to better help this population.…”
Section: Auditory Processing Disorders In Asdmentioning
confidence: 99%
“…They have thus been recommended to evaluate auditory pathway involvement in APD ( AAA, 2010 ; Ankmnal-Veeranna, Allan, & Allen, 2019 ; ASHA, 2005 ; Jerger & Musiek, 2000 ). However, studies using these techniques have produced inconsistent findings, probably due to varying definitions of APD, retrospective design, inadequate methodologic control, small group sizes, or lack of a control group ( Liu, Zhu, Chen, Hong, & Chi, 2021 ).…”
Section: Introductionmentioning
confidence: 99%